2021
DOI: 10.1002/acm2.13432
|View full text |Cite
|
Sign up to set email alerts
|

Determining the longitudinal accuracy and reproducibility of T1 and T2 in a 3T MRI scanner

Abstract: To determine baseline accuracy and reproducibility of T 1 and T 2 relaxation times over 12 months on a dedicated radiotherapy MRI scanner. Methods: An International Society of Magnetic Resonance in Medicine/National Institute of Standards and Technology (ISMRM/NIST) System Phantom was scanned monthly on a 3T MRI scanner for 1 year. T 1 was measured using inversion recovery (T 1 -IR) and variable flip angle (T 1 -VFA) sequences and T 2 was measured using a multi-echo spin echo (T 2 -SE) sequence. For each vial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Saturation was mainly investigated due to past studies completed on the same MRI scanner having identified similar effects when undertaking phantom imaging. 26 Further investigations, out of the scope of this study, would be required to find the cause and factors affecting the signal saturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saturation was mainly investigated due to past studies completed on the same MRI scanner having identified similar effects when undertaking phantom imaging. 26 Further investigations, out of the scope of this study, would be required to find the cause and factors affecting the signal saturation.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is not easy to detect: in the offline computed ADC maps, saturation was found to primarily affect the SDs derived from the DWI‐ADC fit, while minimally impacting the actual ADC value. Saturation was mainly investigated due to past studies completed on the same MRI scanner having identified similar effects when undertaking phantom imaging 26 . Further investigations, out of the scope of this study, would be required to find the cause and factors affecting the signal saturation.…”
Section: Discussionmentioning
confidence: 99%
“…T1 and T2 mapping, for example, are indexes that determine free water content [ 18 ] and tissue morphology [ 19 ], respectively. Though they have shown potential for the determination of early tumor progression in the brain [ 20 ], long MRI acquisition times and limits of one acquisition per quantitative map [ 21 , 22 , 23 ] have prevented the day-to-day adoption of conventional quantitative relaxometry in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The International Society for Magnetic Resonance in Medicine (ISMRM) and the National Institute of Standards and Technology (NIST) developed a calibration phantom, 1,2 consisting of 14 spheres filled with nickel chloride (NiCl 2 ) solutions of various concentrations, that has been used to validate T1 mapping techniques, as well as for reproducibility comparisons across platforms and sites. The T1 relaxation times of the 14 T1 spheres carefully measured by NMR are available from the NIST to serve as reference or ground truth T1 values at a range of temperatures for 1.5 and 3 T. 2 The ISMRM/NIST system phantom has thus demonstrated its utility in a large body of research at 1.5 and 3 T for the validation of quantitative methods and assessment of multivendor and multisite repeatability (see 1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16] and the references therein). However, the reference T1 values at 7 T are not available from the NIST.…”
Section: Introductionmentioning
confidence: 99%
“…The T1 relaxation times of the 14 T1 spheres carefully measured by NMR are available from the NIST to serve as reference or ground truth T1 values at a range of temperatures for 1.5 and 3 T 2 . The ISMRM/NIST system phantom has thus demonstrated its utility in a large body of research at 1.5 and 3 T for the validation of quantitative methods and assessment of multivendor and multisite repeatability (see 1,3–16 and the references therein). However, the reference T1 values at 7 T are not available from the NIST.…”
Section: Introductionmentioning
confidence: 99%